The Impact of Independent Curriculum on Human Development Index in Islamic Religious Education in Indonesia - Lailatul Badriah (Magister Programme Of Islamic Education Departement at Institut Agama Islam Tarbiyatut Tholabah, 2025)
The purpose of this article is to explore the contribution of the Independent Curriculum to the improvement of the Human Development Index (HDI) in Indonesia in IRE and to assess the effectiveness of the Independent Curriculum in improving the quality of PAI learning. The method used in this study is literature with a qualitative approach using data collection from related data sources. The results of the study show that the Human Development Index (HDI) is an important indicator to measure the quality of human life. The Independent Curriculum, as the latest initiative in the field of education, is expected to be able to contribute significantly to the improvement of HDI. Evaluation and monitoring of the implementation of the Independent Curriculum in Islamic Religious Education (IRE) is the key to ensuring its effectiveness in improving the quality of education and HDI. Despite the challenges, there is a great opportunity to strengthen HDI through proper adaptation and implementation. The concept of curriculum in the context of IRE requires adjustment and innovation, which in turn encourages the preparation of learning plans based on the Independent Curriculum. Consistent and measurable implementation of the Independent Curriculum in IRE is expected to create a superior and highly competitive generation. In addition, this curriculum also contributes to the improvement in each student's problem-solving and fosters each student's creativity. These findings are expected to provide a basis for more effective education policies to support human development in Indonesia.